Clusterin Is Required for β-Amyloid Toxicity in Human iPSC-Derived Neurons - Robbins, Jacqueline P.; Perfect, Leo; Ribe, Elena M.; Maresca, Marcello; Dangla-Valls, Adrià; Foster, Evangeline M.; Killick, Richard; Nowosiad, Paulina; Reid, Matthew J.; Polit, Lucia Dutan; Nevado, Alejo J.; Ebner, Daniel; et al. (Frontiers in Neuroscience, 2018)
Our understanding of the molecular processes underlying Alzheimer’s disease (AD) is still limited, hindering the development of effective treatments and highlighting the need for human-specific models. Advances in identifying components of the amyloid cascade are progressing, including the role of the protein clusterin in mediating β-amyloid (Aβ) toxicity. Mutations in the clusterin gene (CLU), a major genetic AD risk factor, are known to have important roles in Aβ processing. Here we investigate how CLU mediates Aβ-driven neurodegeneration in human induced pluripotent stem cell (iPSC)-derived neurons. We generated a novel CLU-knockout iPSC line by CRISPR/Cas9-mediated gene editing to investigate Aβ-mediated neurodegeneration in cortical neurons differentiated from wild type and CLU knockout iPSCs. We measured response to Aβ using an imaging assay and measured changes in gene expression using qPCR and RNA sequencing. In wild type neurons imaging indicated that neuronal processes degenerate following treatment with Aβ25-35 peptides and Aβ1-42 oligomers, in a dose dependent manner, and that intracellular levels of clusterin are increased following Aβ treatment. However, in CLU knockout neurons Aβ exposure did not affect neurite length, suggesting that clusterin is an important component of the amyloid cascade. Transcriptomic data were analysed to elucidate the pathways responsible for the altered response to Aβ in neurons with the CLU deletion. Four of the five genes previously identified as downstream to Aβ and Dkk1 proteins in an Aβ-driven neurotoxic pathway in rodent cells were also dysregulated in human neurons with the CLU deletion. Alzheimer’s disease and lysosome pathways were the most significantly dysregulated pathways in the CLU knockout neurons, and pathways relating to cytoskeletal processes were most dysregulated in Aβ treated neurons. The absence of neurodegeneration in the CLU knockout neurons in response to Aβ compared to the wild type neurons supports the role of clusterin in Aβ-mediated AD pathogenesis.